Priming with mindfulness affects our capacity to self-regulate brain activity? - Costa, Nuno M. C. da (2020)
Self-regulation (SR) is a vital adaptation process to environmental and social challenges. Indispensable in our growing hyper-technological and hyper-stimulative society. SR deficits are associated with diverse behavioral problems and mental disorders such as depression, rumination, distraction, anxiety, stress, and attention control. Neurofeedback Training (NFT) is one of the techniques to train brain self-regulation (BSR). In the current protocols, the benefits from NFT greatly differ between subjects, with a high percentage of inefficacy. Therefore, understanding how to prime self-regulation could be the key to unlock predictors and optimize the success of Neurofeedback modulation, and vice-versa. Literature hypothesizes that the 'optimal' state of SR learning is reached when irrelevant associations between internal states and external reward are avoided, and when the learner stays engaged, focused and undistracted. Thus, suggesting a close relation to focused attention forms of mindfulness meditation (MM). As such, to promote this 'optimal' self-regulation on an NFT protocol, we implemented a human-computer framework to assist the subject to voluntary modulate their brain activity. The assistance was done by priming the subject with mindfulness guided instructions right before the NFT. In conclusion, conducting this intervention was the first step to determine if priming with external neurostimulation would enhance Neurofeedback self-regulation.